THE EFFECT OF USING THINK- PAIR-SHARE STRATEGY ON STUDENTS’ SPEAKING SKILL AT EIGHT GRADE UPT SMPN 1 SITIUNG - Martiya Nurni Khairita; Dodi Widia Nanda; Nurhidayati (STKIP Subang, 2024)
This research discusses analysis which aims to determne the use of think pair share strategy to improve students’ speaking skills. The subjects of this research were eight grade students at UPT SMPN 1 Sitiung for the 2023/2024 academic year. The method used in this research was carried out in two classes, the experimental class and control class. The population of this study were eight grade student at UPT SMPN 1 Sitiung and the sample was VIII B consisting of 29 students as the experimental class and class VIII A consisting of 29 students as the control class. The instrument used in this research was a test. this test is given in the from of an initial test and a final test. the result of this research show that there is an influence oh Think-Pair-Share on student’ speaking skill abilities. This is supported by the results of students’ speaking ability scores in the experimental class, namely 77.75, while in the control class it was 66.89, Furrthermore, based on the results of the analysis of data collection using the normality test, a post test experiment value of 0.015 > 0.05 was obtained. Based on these results, it can be conluded that there is an influence of using Think-Pair-Share to teach students’ speaking skills at the junior high level, especially UPT SMPN 1 Sitiung.